(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
This article presents an analysis of the threats and risks that may arise in the implementation of voice-based applications. In particular, the issues of classifying threats according to the STRIDE (Spoofing, Tampering, Repudiation, Information disclosure, Denial of Service, Elevation of privileges) methodology, assessing threat risks according to the DREAD (Damage Potential, Reproducibility, Exploitability, Aﬀected Users, Discoverability) model, and taking protective measures against them are considered [1,2].